P119 Surgical recurrence in Crohn's disease patients with severe post-operative endoscopic recurrence: risk difference between purely anastomotic lesions and lesions limited to the neoterminal ileum. (25th January 2019) - Mocciaro, F; Giunta, M; Di Mitri, R; Scimeca, D; Renna, S; Conte, E; Bonaccorso, A; Cappello, M; Scrivo, B; Casà, A; Malizia, G; Cottone, M; et al.
Abstract: Background: Seventy per cent of patients with Crohn's disease (CD) require surgery. Post-operative endoscopic recurrence (POR) is up to 100% at 5 years with severe POR at 6-month around 50% as reported in an Italian study. Surgical recurrence is strongly related to the severity of POR with higher rate in those with 'very severe' POR (i3 and i4) lesions. It is quite unclear if lesions limited to the neoterminal ileum modify the risk of surgical recurrence compared with purely anastomotic lesions. The STRIDE study tried to stress the difference between 2a (purely anastomotic lesions) and 2b (>5 aphthous ulcers in the neoterminal ileum) lesions to better identify POR with worst prognosis. We performed a pilot study to compare 2a and 2b lesions in terms of surgical recurrence. Methods: We reviewed all colonoscopies performed in CD patients who have undergone ileocolonic resection regardless of the year of surgery. We analysed data from endoscopies performed in 2016, to reach an adequate follow-up until the end of 2018. POR was evaluated according to the Rutgeerts' score classifying severe POR in those with a score ≥ i2. The main outcome was surgical recurrence. Results: After reviewing the electronic medical records, 64 CD patients were identified: 6 with a Rutgeerts' score ≤ i1 and 58 (91%) with a score ≥ i2 . Considering only those with severe POR, 43/58 (74%) presented a score of i3 or i4 (very severe POR): 33 male (57%) with overall mean age of 46.8 ± 14.9 year, 42 (72%) and 16 (28%) were treated, respectively, with biological therapies or immunosuppressants. Thirty-nine patients (67%) presented both neoterminal ileum and anastomotic lesions, 14 (24%) presented purely anastomotic lesions (2a), and 5(9%) presented only lesions in the neoterminal ileum (2b). At the end of the follow-up (2 years), 5 patients of 58(9%) underwent new surgery and those with 2b lesions presented a significantly increased risk compared with those with 2a lesions ( p < 0.0001). Conclusions: This pilot retrospective study seems to confirm that in CD patients, with severe POR, only 2b lesions should be considered the worst prognostic factor for surgical recurrence. POR that involves neoterminal ileum probably increases the risk of surgery during the follow-up. Lesions limited to the anastomosis cannot be considered severe POR deserving of an aggressive medical treatment.